(adsbygoogle = window.adsbygoogle || []).push({}); "on the relativity of times"

tB - tA = rAB / (c - v) and t'A - tB = rAB / (c + v)

"The Principle of Relativity", p 42, by A. Einstein.

consequently,

c = [rAB / (tB - tA)] + v and c = [rAB / (t'A - tB) - v

let rAB = x' and (tB - tA) = t' so that

c = (x' / t') + v

since x' = x - v*t

c = [(x - v*t) / t'] + v so that

x = t'*(c - v) + v*t

and let rAB = x and (t'A - tB) = t so that

c = (x / t) - v so that

x = t*(c + v)

consequently,

t'*(c - v) + v*t = t*(c + v)

t'*(c - v) = t*(c + v) - v*t

t'*(c - v) = t*c

t' = t*c / (c - v)

t' = t / (1 - v / c)

t' is not t / sqrt(1 - v^2 / c^2). why? thanks! (6:00 pm thru 7:00 pm, 9/21/2006)

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# On the relativity of times

**Physics Forums | Science Articles, Homework Help, Discussion**